Simulación financiera aplicada a la valoración del riesgo de crédito con el modelo de opciones (2019)
This paper presents financial simulation as the best alternative for valuating credit risk with the Merton Model on a real option. We propose this in contrast to the Black and Scholes model introduced by Hull, Nelken and White in 2004 for the same case study. To demonstrate this, we begin by reviewing the basic concepts of a financial option. Then we present the Black-Scholes model for the valuation of European options with special emphasis on the assumptions and the limitations that this possibility implies. We introduce the analogy between real options and financial options that allows the measurement of credit risk on investment opportunities. We explain the Merton model, and finally, we propose financial simulation as a general and powerful methodology to quantify credit risk in the Merton model, including an application on an investment project with “Crystal Ball”.